Arbuscular mycorrhiza-specific signaling in rice transcends the common symbiosis signaling pathway. - Gutjahr, C; Banba, M; Croset, V; An, K; Miyao, A; An, G; Hirochika, H; Imaizumi-Anraku, H; Paszkowski, U (2008)
Knowledge about signaling in arbuscular mycorrhizal (AM) symbioses is currently restricted to the common symbiosis (SYM) signaling pathway discovered in legumes. This pathway includes calcium as a second messenger and regulates both AM and rhizobial symbioses. Both monocotyledons and dicotyledons form symbiotic associations with AM fungi, and although they differ markedly in the organization of their root systems, the morphology of colonization is similar. To identify and dissect AM-specific signaling in rice (Oryza sativa), we developed molecular phenotyping tools based on gene expression patterns that monitor various steps of AM colonization. These tools were used to distinguish common SYM-dependent and -independent signaling by examining rice mutants of selected putative legume signaling orthologs predicted to be perturbed both upstream (CASTOR and POLLUX) and downstream (CCAMK and CYCLOPS) of the central, calcium-spiking signal. All four mutants displayed impaired AM interactions and altered AM-specific gene expression patterns, therefore demonstrating functional conservation of SYM signaling between distant plant species. In addition, differential gene expression patterns in the mutants provided evidence for AM-specific but SYM-independent signaling in rice and furthermore for unexpected deviations from the SYM pathway downstream of calcium spiking.